Activities test of Mahkota Dewa (Phaleria macrocarpa) leaves extract against Candida albicans of HIV/AIDS patients - Elianora, Dewi; B., Busman; Amrilya, Yeri (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2017)
ABSTRACTIntroduction: Candida albicans is a local commensal flora of the oral cavity, with opportunistic nature and often causes oral candidiasis in HIV/AIDS patients. Since long time, Mahkota Dewa (Phaleria macrocarpa) known of having efficacy treat various disease traditionally. The purpose of this study was to determine the activity test of Phaleria macrocarpa leaves extract against Candida albicans from HIV/AIDS patients. Methods: Experimental laboratory with samples colonies of the Candida albicans fungus obtained from patients with HIV/AIDS at Dr. M. Djamil General Hospital Padang. Research conducted during January-March 2016 in Microbiology and Chemistry Laboratory of Kopertis Region X, Microbiology Laboratory of Dr. M. Djamil General Hospital, and Microbiology Laboratory of Siti Rahmah Islamic Hospital, Padang, West Sumatra. Data analyzed using the Kruskal-Wallis test. Results: The concentration of the Phaleria Macrocarpa leaves extract used in this study was 10, 20, 40 and 80%. Inhibition zone average value obtained 0,00 mm, means no inhibition zone, 9.217 mm and 18.017 mm with sig = 0.000 <0.05. Conclusion: The higher level of the Phaleria macrocarpa leaves extract concentration, the higher inhibition zone diameter against Candida albicans, with the highest in concentration 80%.Keywords: Mahkota Dewa (Phaleria macrocarpa) leaves extract, Candida albicans, HIV/AIDS